NEO-REVIVALIST MOVEMENTS IN HINDUISM AND THEIR CHALLENGES TO HINDU FUNDAMENTALISM - M. Sivakumara Swamy (Journal of Dharma, 1990)
The long history of Hinduism is marked by alternating periods of decadence and renaissance. The first phase of Hinduism is represented by the hymns of the Rig gveda. These hymns reveal a progress from the worship of the personified powers of nature to the realization of the Absolute Spirit. The most notable development of the gvedic Age is the conception of lJ.ta which stands for the triple order, cosmic, moral and sacrificial. The cosmic order was then supposed to be maintained by the sacrifice (yejna). It is from this Rts that the ideals of Dharma and the Law of Karma are derived. This age of fruitful evolution of theistic and philosophical ideas followed by the age of Brahma Ji-texts. During this period, the sacrificial cult grew so complex and elaborate as to appear mechanical and soul-less. A great magical value came to be attached to the meticulous performance of yajna and the priestly class became all- powerful and supreme. The idea of verns-asreme-dberms began to have its influence over the minds of the people. This was a period of decadence from the point of view of intellectual development. This was followed by a period of renaissance represented by the Upenised, It was during this age that contemplation took the place of worship and the acquisition of divine knowledge gained precedence over the performance of rites and ceremonies.